The Brothers Kennedy : John, Robert, Edward - Krull, Kathleen; Bates, Amy June (New York : Simon & Schuster Books for Young Readers, 2010)
Presents a pictorial biography of three Kennedy brothers--John, Robert, and Edward--and focuses on the political ambitions of the Kennedy family and their strong family bonds throughout the years.
Includes bibliographical references (p. 40).
Keywords: Kennedy, John F -- 1917-1963; Kennedy, Robert F., -- 1925-1968; Kennedy, Edward M -- 1932-2009; Kennedy family; United States -- Congress -- Biography; Presidents -- Biography -- United States; Legislators -- Biography -- United States; Brothers -- Biography